Simplify 7/9h +10-4/9h-3

1 answer

To simplify the expression 7/9h + 10 - 4/9h - 3, we can combine like terms.

First, let's combine the terms with "h".

The equation becomes (7/9h - 4/9h) + 10 - 3.

Simplifying further, we subtract the coefficients of "h":

3/9h + 10 - 3.

Now, let's simplify the remaining terms:

3/9h is equivalent to 1/3h.

The expression becomes 1/3h + 10 - 3.

Finally, we combine like terms:

1/3h + 10 - 3 equals 1/3h + 7.

Therefore, the simplified expression is 1/3h + 7.
Similar Questions
  1. simplifying square roots1) find volume of this prism? v=bwh b=√12" w=√6" h=√8" 2)simplify: √576 3)simplify: √400
    1. answers icon 3 answers
  2. Simplify 8a − 2a.Simplify 12e − 5f − 7e +3f. Simplify 9x + 3y − 6 − 5x + 4y −3. Simplify 9/11z − 4/11z. Simplify
    1. answers icon 4 answers
  3. simplifying square roots1) find volume of this prism? v=bwh b=√12" w=√6" h=√8" 2)simplify: √576 3)simplify: √400
    1. answers icon 3 answers
  4. So I need some help on these Graphing Square Root Functions Quiz questions.1. Simplify 2 over √5 2. Simplify -11√112 3.
    1. answers icon 1 answer
more similar questions